Different in Vivo Reactivity Profile in Health Care Workers and Patients with Spina Bifida to Internal and External Latex Glove Surface-Derived Allergen Extracts - Peixinho, CM (2012)
BACKGROUND: Allergy to natural rubber latex is a well-recognized health problem, especially among health care workers and patients with spina bifida. Despite latex sensitization being acquired in health institutions in both health care workers and patients with spina bifida, differences in allergen sensitization profiles have been described between these two risk groups. OBJECTIVE: To investigate the in vivo reactivity of health care workers and patients with spina bifida to extracts of internal and external surfaces of latex gloves and also to specific extracts enriched in major allergens for these risk groups. METHODS: Gloves from different manufacturers were used for protein extraction, and salt precipitation and hydrophobic interaction chromatography (HIC) were applied to obtain the enriched latex extracts. The major latex allergens were quantified by an enzyme immunoassay. The extracts obtained were tested in 14 volunteers using skin prick tests (SPT). RESULTS: Latex glove extracts enriched in the hydrophobic allergens that are most often seen in patients with spina bifida were obtained by selective precipitation, whereas HIC produced extracts enriched in the hydrophilic allergens commonly found in health care workers. The health care workers had positive SPTs to glove extracts from internal surfaces and to the hydrophilic allergen-enriched extracts. By contrast, patients with spina bifida had larger skin reactions both to external glove extracts and to the extracts enriched with the hydrophobic major allergens for this risk group. Despite the protein concentration of these extracts being less than half the concentration of the commercial extract, the weal-and-flare reactions were of similar magnitude. CONCLUSION: Using novel latex extracts, our study showed a different in vivo reactivity pattern in health care workers and in patients with spina bifida to extracts of the internal and external surfaces of gloves, which suggests that sensitization may occur by different routes of exposure, and that this influences the allergen reactivity profiles of these risk groups